2021
DOI: 10.3390/su13042314
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Fire and Energy Performance of Innovative Light-Weight 3D Printed Concrete Wall Configurations in Modular Building System

Abstract: 3D Printed Concrete (3DPC) technology is currently evolving with high demand amongst researches and the integration of modular building system (MBS) with this technology would provide a sustainable solution to modern construction challenges. The use of lightweight concrete in such innovative construction methods offers lightweight structures with better heat and sound insulation compared to normal weight concrete. It is worth noting that fire and energy performance has become central to building design. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…In this context, one can see the benefit of the design flexibility of 3D printing in building complex concrete structures (which are challenging to create with conventional manufacturing methods) with functional geometries in terms of thermo-acoustic damping. For instance, different cavity patterns in wall elements can be easily implemented by additive fabrication to improve the thermal and noise insulation performance while reducing the energy consumption within the life cycle of the concrete structure [35].…”
Section: Energy-efficiency Indicatorsmentioning
confidence: 99%
“…In this context, one can see the benefit of the design flexibility of 3D printing in building complex concrete structures (which are challenging to create with conventional manufacturing methods) with functional geometries in terms of thermo-acoustic damping. For instance, different cavity patterns in wall elements can be easily implemented by additive fabrication to improve the thermal and noise insulation performance while reducing the energy consumption within the life cycle of the concrete structure [35].…”
Section: Energy-efficiency Indicatorsmentioning
confidence: 99%
“…Therefore, researchers previously investigated some 3D-printed concrete non-load-bearing wall panels with different cross-sectional configurations, such as triangular, lattice, and sinusoid, with a focus on investigating fire resistance and thermal behaviour under standard fire conditions and different real fire circumstances. (i.e., hydrocarbon fire, rapid fire, and prolonged fire) [16,17,30,50].…”
Section: Performance Of 3dcp Structures Under Elevated Temperaturementioning
confidence: 99%
“…Besides, Nguyen et al [29] suggested that the 3D printed cellular structure has extensive application prospects such as coastal protection blocks, noise insulation panels and so on. To compare the fire performance of varying 3D printed concrete walls, the finite element analysis was carried by Suntharalingam et al [43] and the results showed that 3D printed non-load bearing cavity walls had superior fire resistance. To create an energy-saving and comfortable environment, a guideline was presented by Alkhalidi et al [44] by investigating the thermal comfort of 3D printed structures.…”
Section: Structural-functional Formmentioning
confidence: 99%